Možnosti využití výlisků z plodů aronie - Kujínková, Jana (Vysoké učení technické v Brně. Fakulta chemická, 2017)
Tato diplomová práce se zabývá možnostmi využití výlisků z plodů aronie. Teoretická část je zaměřena na botanickou charakteristiku aronie, popis HPLC a anthokyanových barviv. V experimentální části se zkoumají různé vlivy extrakčních podmínek na obsah vybraných polyfenolických sloučenin, kyseliny gallové a vanilové, katechinu a rutinu, ve výliscích z plodů aronie. Zmíněné sloučeniny byly v této práci stanoveny metodou HPLC, stejně jako jednoduché sacharidy. Množství anthokyanových barviv bylo zjištěno pH diferenciální metodou.

This diploma thesis deals with possibilities of using of aronia fruit pomace. The theoretical part is focused on botanical characteristics of aronia fruit, description of HPLC and anthocyanins dyes. The effects of various extraction condition on content of some polyphenolic compounds (gallic and vanilla acids, katechin and rutin) in aronia berry pomace are investigated in the experimental part. The mentioned compounds were detected with HPLC. Thanks to this method the content of carbohydrates was also detected. A quantity of anthocyanins dyes was determined by pH differential method.
The possibility of using of Aronia fruit pomace
Keywords: Aronie; anthokyany; HPLC; výlisky; pH diferenciální metoda; polyfenolické sloučeniny; Aronia melanocarpa; anthocyanins; HPLC; pomace of black chokeberry; pH differential method; polyphenolic compounds